-7x-12=2x-(5x-8)

Simple and best practice solution for -7x-12=2x-(5x-8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7x-12=2x-(5x-8) equation:


Simplifying
-7x + -12 = 2x + -1(5x + -8)

Reorder the terms:
-12 + -7x = 2x + -1(5x + -8)

Reorder the terms:
-12 + -7x = 2x + -1(-8 + 5x)
-12 + -7x = 2x + (-8 * -1 + 5x * -1)
-12 + -7x = 2x + (8 + -5x)

Reorder the terms:
-12 + -7x = 8 + 2x + -5x

Combine like terms: 2x + -5x = -3x
-12 + -7x = 8 + -3x

Solving
-12 + -7x = 8 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
-12 + -7x + 3x = 8 + -3x + 3x

Combine like terms: -7x + 3x = -4x
-12 + -4x = 8 + -3x + 3x

Combine like terms: -3x + 3x = 0
-12 + -4x = 8 + 0
-12 + -4x = 8

Add '12' to each side of the equation.
-12 + 12 + -4x = 8 + 12

Combine like terms: -12 + 12 = 0
0 + -4x = 8 + 12
-4x = 8 + 12

Combine like terms: 8 + 12 = 20
-4x = 20

Divide each side by '-4'.
x = -5

Simplifying
x = -5

See similar equations:

| (k-8)/(4+k)=-0.2 | | 7+n/8=n | | 0=a-49 | | ((-3j-(-4))/-6)-8=12 | | -3x+4-2x=7x | | -7-10=3f-10 | | -y/4=-10 | | 16x=0.5 | | -1(z+5)=-1 | | 50+7x-6=13x-4 | | 2x^5/2+5x^3/2=7x^1/2 | | 12=3b-5b | | -7f-10=3f-10 | | 7/1(4/1) | | 7/1(4/1) | | -1(2+5)=-14 | | 53y=2 | | 4n^2-2=14 | | -3n=7n+10 | | 22x+2y=-20 | | 5a+45a+23b+5=25a+3b+56 | | 4/3x=6 | | 15y+10=160+40y | | 96=-6x+5(-x-5) | | 2x(x+1)=7 | | 8p-1+p=10p-9 | | 2z-3=53+9z | | 4+3y=-12 | | -17=4x+12-9x | | 3x-5/x-1=3x-2/x+2 | | -0.4p=0.2p+9 | | -7x+1=6 |

Equations solver categories